Exposure to cyanobacteria: acute health effects associated with endotoxins. (May 2016) - Lévesque, B.; Gervais, M.-C.; Chevalier, P.; Gauvin, D.; Anassour-Laouan-Sidi, E.; Gingras, S.; Fortin, N.; Brisson, G.; Greer, C.; Bird, D.
Highlights: The relationship between exposure to endotoxins and health symptoms was examined. Water contact with endotoxins was linked to gastrointestinal symptoms. Mechanisms linking endotoxins and gastrointestinal symptoms should be investigated.